Association Between Staphylococcus aureus Bacteremia and Hospital Mortality in Hemodialysis Patients With Bloodstream Infection: A Multicenter Cohort From Japanese Tertiary Care Centers. Issue 4 (12th May 2017) - Imaizumi, Takahiro; Hasegawa, Takeshi; Nomura, Atsushi; Sasaki, Sho; Nishiwaki, Hiroki; Ozeki, Takaya; Shimizu, Hideaki; Minatoguchi, Shun; Yamakawa, Taishi; Yazawa, Masahiko; Uchida, Daisuke; Kawarazaki, Hiroo; et al.
Abstract: Multiple studies have shown that Staphylococcus aureus bacteremia (SAB) has been a major cause of death in hemodialysis patients. We examined whether SAB is a risk for mortality among chronic hemodialysis patients in Japan where the standard vascular access is arteriovenous fistula (AVF). This was a multicenter, retrospective study of maintenance hemodialysis patients with bloodstream infection (BSI) from 2011 to 2013 at tertiary care centers in Japan. The endpoint was hospital mortality. Our cohort contained 32 SAB cases (14 MRSA and 18 MSSA) and 42 non‐SAB cases. Hospital mortality was higher among SAB cases than non‐SAB cases (46.9% vs. 23.8%, P  = 0.038). In patients with BSI, SAB was significantly associated with hospital mortality after adjustment for potential confounders, including type of vascular access (OR 3.26). S. aureus was the leading cause of BSI and hospital mortality among this cohort. Therefore, initial empiric treatment should cover for S. aureus .